The emperors of the schizophrenia polygene have no clothes - Crow, T (Cambridge University Press, 2008)
A substantial body of research literature, identified by nine out of ten papers on genetics in the recent ISI research front on schizophrenia, claims to have established associations between aspects of the disease and sequence variation in specific candidate genes. These candidatures have proven unreplicated in large sibling pair linkage surveys and a targeted association study. Even if the case for an association be regarded as a lucky guess (assuming one gene in 30,000 was guessed right) the large linkage and association studies provide no evidence of sequence varation relating to psychosis at any of these gene loci. Thus this body of work must be regarded as an indicator of the extent to which the 'eye of faith' is able to discern meaning in complex data when none is present.